New Approaches to CSR, Sustainability and Accountability, Volume III - Çalıyurt, Kıymet Tunca (Accounting, Finance, Sustainability, Governance & Fraud: Theory and Application, 2022)
XLVII, 239 p. 18 illus., 13 illus. in color.